2022
DOI: 10.3390/microorganisms10071351
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Gut Microbial Communities of Broiler Chicken Fed Black Soldier Fly Larvae-Desmodium-Based Meal as a Dietary Protein Source

Abstract: The utilization of insect-based diets to improve gastrointestinal function and gut health in poultry is gaining global attention as a promising feed additive. The objective of this study was to determine the optimal inclusion level of the full-fat black soldier fly larvae (BSFL) and Desmodium intortum (DI) in broiler chicken diets and to evaluate their impact on the microbial community in the gut. The bacterial communities were characterized using Oxford nanopore sequencing of the full-length bacterial 16S rRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…De Souza Vilela et al [86] observed that up to 20% BSFL in diets reduced the abundance of certain bacteria like Enterococcus and unclassified Christensenellaceae, while positively correlating with beneficial butyrate-producing bacteria such as Roseburia and Dehalobacterium. In contrast, Ndotono [141] reported an increase in potentially pathogenic bacteria like Campylobacter and Clostridia at higher BSFL meal inclusion rates, indicating a risk associated with higher concentrations. An analogous finding was reported by another research study, which found that incorporating BSFL at a level of 50% lowered specific constituents of the microbial community residing in the cecum, including potentially pathogenic bacteria like Enterobacteriaceae and the Bacteroides-Prevotella group.…”
Section: Gastrointestinal Health and Microbiotamentioning
confidence: 80%
See 1 more Smart Citation
“…De Souza Vilela et al [86] observed that up to 20% BSFL in diets reduced the abundance of certain bacteria like Enterococcus and unclassified Christensenellaceae, while positively correlating with beneficial butyrate-producing bacteria such as Roseburia and Dehalobacterium. In contrast, Ndotono [141] reported an increase in potentially pathogenic bacteria like Campylobacter and Clostridia at higher BSFL meal inclusion rates, indicating a risk associated with higher concentrations. An analogous finding was reported by another research study, which found that incorporating BSFL at a level of 50% lowered specific constituents of the microbial community residing in the cecum, including potentially pathogenic bacteria like Enterobacteriaceae and the Bacteroides-Prevotella group.…”
Section: Gastrointestinal Health and Microbiotamentioning
confidence: 80%
“…According to several studies, the inclusion of BSFL in chicken diets has been linked to both beneficial and harmful impacts on the gut microbiota. Ndotono et al [140] found that a diet with 75% BSFL significantly increased beneficial lactic acid bacteria, enhancing gut microbiota diversity. However, Biasato et al [132] noted that while a 5% inclusion of BSFL meal fostered beneficial genera, a 15% inclusion led to reduced microbial complexity and an increase in mucolytic bacteria, potentially harming gut health.…”
Section: Gastrointestinal Health and Microbiotamentioning
confidence: 99%
“…The dietary components of poultry have a major impact on the gut microbiota which is essential for digestion and uptake, growth and overall health condition (Torok et al, 2011) and (Oakley et al, 2014). Global interest is growing in the application of insect-based diets as a potential feed additive to enhance gut health and gastrointestinal function in poultry (Ndotono et al, 2022). BSF larvae contain an antimicrobial peptide (AMP) that inhibits the growth of a variety of harmful bacteria, as well as monolaurin compounds derived from lauric acid that have antibacterial properties, which damage bacteria's lipid membrane (Park et al, 2014) and (Abd El-hack et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…According to Lee et al (2018), the BSF larva may have a positive impact on the immunity and ability to survive a salmonella infection. Abd El-Hack et al (2020) and Ndotono et al (2022) recorded an increase in the lactic acid bacteria (LAB) in the diets that included BSF larvae, particularly with 75% This rise due to the presence of chitin in the BSF larvae diet. Borrelli et al (2017) found that Chitin is naturally a polysaccharide which can be fermented by microbes broke down by short chain fatty acid producing bacteria, it can also serve as a meal for microbes.…”
Section: Discussionmentioning
confidence: 99%
“…Given the beneficial effects of BSFL-incorporated diets on growth performance and gut microbiota in birds, several studies have insight into the profiles of microbial communities harbored in poultry gut microbiota. Firmicutes , Bacteroidetes , Proteobacteria , and Actinobacteria are identified as predominant phyla across the dietary treatment [ 13 ]. Additionally, feeding with a low level of BSFL (10%) to layers leads to an increase in caecal microbial diversities [ 14 ].…”
Section: Introductionmentioning
confidence: 99%